Differences in intelligence test scores among urban children in Ghana: Examining test characteristics and socio-economic factors - Anum, A. (University of Ghana, 2015)
Performance on standardized cognitive tests among children in low income or less developed countries have consistently been low. The difference in test scores usually range between 1 to 2 standard deviations lower than published norms. Explanations for this difference have been attributed partly to IQ differences between different races which has been a subject of debate in scientific and academic research since the inception of IQ testing in the early 20th century. The debate about race differences in intelligence concerns the interpretation of research findings that Caucasian test takers tend on average to score higher than individuals of African descent. This was followed subsequently with the finding that test takers of East Asian background tend to score higher than Caucasians. Part of the explanation for racial differences in IQ or test scores is the issue of test bias, that is, test items tend to favor individuals for whom the test was initially developed. Although tests are standardized on local populations to address this challenge, significant differences are still found between groups separated by socioeconomic factors, even on measures that are supposed to be culture-fair. It therefore appears that differences in test scores may be explained by other factors apart from cultural differences. In the current study, we examined performance on three tests with varying degrees of cultural bias. We examined the effects of different socioeconomic factors on test performance and found expected superior performance for children in high socioeconomic groups on all tests. The difference in scores however diminished on tests that had low cultural bias. The findings from this study are discussed in the light of differences in wealth, parents' influence, and quality of school and teaching.
School of social sciences colloquium
Keywords: IQ differences; African descent; socioeconomic groups; cultural bias